2006
DOI: 10.1682/jrrd.2005.04.0068
|View full text |Cite
|
Sign up to set email alerts
|

Functional electrical stimulation reinforced tenodesis effect controlled by myoelectric activity from wrist extensors

Abstract: Abstract-We demonstrated a method for enhancing the tenodesis grip in individuals with sustained tetraplegia with spinal cord lesion at the C6-C7 neurological level. Subjects used the myoelectric activity from wrist extensor muscles to directly control the electrical stimulation of the extrinsic finger and thumb flexors (flexor pollicis longus and flexor digitorum superficialis/profondus) with the use of a specially designed system, Myoelectrically Controlled Functional Electrical Stimulation (MeCFES). We scre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 17 publications
(34 reference statements)
0
20
0
2
Order By: Relevance
“…Our study demonstrated that FES increases finger-opening distance but decreases wrist extension angle, while WHO use slightly decreases finger opening distance, maybe due to the tenodesis effect [17], but increases wrist extension angle. A balance between finger opening distance and wrist extension angle is required for function.…”
Section: Choice Of Fes/who For Assisting Hand Opening While Keeping Tmentioning
confidence: 60%
“…Our study demonstrated that FES increases finger-opening distance but decreases wrist extension angle, while WHO use slightly decreases finger opening distance, maybe due to the tenodesis effect [17], but increases wrist extension angle. A balance between finger opening distance and wrist extension angle is required for function.…”
Section: Choice Of Fes/who For Assisting Hand Opening While Keeping Tmentioning
confidence: 60%
“…The FES system can also be a feasible solution for resolving the radial wrist extensors bias [18,[21][22]. Thorsen et al devised a myoelectrically controlled single-channel FES system to reinforce the tenodesis grasp in persons with C6 and C7 tetraplegia and found an imbalance of hand grasping muscles that resulted in reducing the grasp capability [18].…”
Section: Discussionmentioning
confidence: 99%
“…Until now, other rehabilitative approaches also have been attempted to improve hand function in persons with tetraplegic SCI [18][19][20][21][22][23][24][25]. Functional electrical stimulation (FES) enables persons with tetraplegia to restore grasp function [18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations